1998
DOI: 10.1111/j.1600-0447.1998.tb09957.x
|View full text |Cite
|
Sign up to set email alerts
|

The familial aggregation of adolescent suicide attempts

Abstract: The objective of this study was to determine whether the familial aggregation of suicidal behaviour is explained by the familial aggregation of personality disorder and aggression. The relatives of 62 clinically referred adolescent suicide attempters were compared with 70 never-suicidal psychiatric controls. The first-degree relatives of the suicide attempters had a higher rate of suicide attempts/completion than those of the psychiatric controls. This rate remained significantly higher after controlling for A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
68
0
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(79 citation statements)
references
References 34 publications
9
68
0
2
Order By: Relevance
“…These studies also support a definition of the clinical phenotype that includes suicidal behavior, but does not include suicidal ideation, insofar as Pfeffer and colleagues found that a family history of attempts was increased only in the relatives of proband attempters but not in the relatives of proband ideators (21). A relationship between familial transmission of suicidal behavior and of impulsive aggression was also supported, since a higher rate of assaultive behavior was reported in the relatives of proband suicide attempters (21), and conversely, a higher rate of suicidal behavior in relatives was reported in the relatives of those proband attempters with higher levels of impulsive aggression (26).…”
Section: Family Studies Of Suicide Attempting Probands (Seementioning
confidence: 80%
“…These studies also support a definition of the clinical phenotype that includes suicidal behavior, but does not include suicidal ideation, insofar as Pfeffer and colleagues found that a family history of attempts was increased only in the relatives of proband attempters but not in the relatives of proband ideators (21). A relationship between familial transmission of suicidal behavior and of impulsive aggression was also supported, since a higher rate of assaultive behavior was reported in the relatives of proband suicide attempters (21), and conversely, a higher rate of suicidal behavior in relatives was reported in the relatives of those proband attempters with higher levels of impulsive aggression (26).…”
Section: Family Studies Of Suicide Attempting Probands (Seementioning
confidence: 80%
“…Finally and importantly, unelucidated familial influences appear to contribute to youth suicidal behavior. There have been many reports of familial aggregation of suicidal behavior in adults (e.g., Egeland and Sussex, 1985) and a few family studies of youth suicidal behavior as well (Brent et al, 1996a;Bridge et al, 1997;Gould et al, 1996;Johnson et al, 1998), which all found familial factors even when controlling for psychiatric disorders.…”
Section: Nih Public Accessmentioning
confidence: 99%
“…Finally and importantly, unelucidated familial influences appear to contribute to youth suicidal behavior. There have been many reports of familial aggregation of suicidal behavior in adults (e.g., Egeland and Sussex, 1985) and a few family studies of youth suicidal behavior as well (Brent et al, 1996a;Bridge et al, 1997;Gould et al, 1996;Johnson et al, 1998), which all found familial factors even when controlling for psychiatric disorders.Contagion effects have been cited as factors in suicidal behaviors (e.g., Maris, 1997). Although contagion appears to potentially precipitate suicidal behaviors in youth peer groups (Lewinsohn et al, 1994), it has not been found to play a major role in the familial aggregation of suicidal behaviors in either family, adoption, or twin studies (Brent et al, 1996b;Schulsinger et al, 1979; Statham et al, 1998).…”
mentioning
confidence: 99%
“…Estes têm consistentemente indicado que os fatores genéticos conferem uma maior predisposição ao comportamento suicida. Estudos familiares têm apontado para a presença de agregação familiar do comportamento suicida [23][24][25][26][27] (veja tabela 1). Alguns desses estudos conseguiram demonstrar que a transmissão do comportamento suicida é independente da segregação familiar de morbidade psiquiátrica.…”
Section: Genes E Suicídiounclassified